Decreasing grain processing breakage with a novel flexible threshing system: Multivariate optimization and wear investigation. Issue 8 (30th June 2022) - Li, Yibo; Fan, Hongfei; Xu, Yang; Jiang, Jianjun; Cui, Tao; Su, Yuan; Qiao, Mengmeng; Han, Shaoyun; Qian, Jun
Abstract: Decreasing grain processing breakage in traditional rigid threshing units is key to achieving mechanical harvesting with high quality. This work optimizes a novel flexible threshing system with ethylene propylene diene monomer composite nail teeth by a combined experiment—SEM approach. The grain breakage characteristics and parametric ranges under different variables in this system are analyzed. The effects of threshing time on the wear rate, macrostructure, and micromorphology of the rubber layer of ethylene propylene diene monomer composite nail teeth are examined. The results indicate that this system reduces the grain breakage rate in traditional threshing units by 45.96%. Grain breakage rates decrease first and then increase with increasing rotational speed and obliquity of the cylinder. Breakage rate is inversely proportional to concave clearance and positively proportional to feeding rate. The wear rate of the rubber layer decreases first and then increases as threshing time increases. Macroscopically, fine cracks distributed differently, laterally, and vertically evolve into divergent pits. Microscopically, fish‐scale wearing marks change into faults with varying morphology. Practical applications: Based on a self‐made threshing system with ethylene propylene diene monomer composite nail teeth, the elastic collision and flexible threshing of corn during threshing are realized in this study. By optimizing the process parameters of the threshing system and analyzing the wear performance of the nail teeth, the breakage rates and non‐threshing rates of grains in the traditional threshing system are reduced. These findings provide a basis for reducing the breakage and loss of agricultural products.